# Evaluate the following expression using the given values: find x - 3y if x = 3 and y = -2?

-9, -3, 3, 9

**Solution:**

The given expression is (x - 3y)

We can evaluate an algebraic expression if we input the values of the unknown variables.

If x = 3 and y = -2

Substituting it in the expression we get

= 3 - 3(-2)

By further calculation

= 3 + 6

By adding both the terms

= 9

Therefore, x - 3y is 9.

## Evaluate the following expression using the given values: find x - 3y if x = 3 and y = -2?

**Summary:**

The value of x - 3y is 9 if x = 3 and y = -2.